Screening of drought tolerant foxtail millet (Setaria italica beauv) germplasm - Begum, F; Sultana, R; Nessa, A (Bangladesh Journal of Scientific and Industrial Research, 2014)
A field experiment on foxtail millet was laid out under irrigated and rainfed condition to screen semi drought tolerant lines. Parameters studied, like plant height, total dry matter accumulation and yield decrease under rainfed condition as compared to that under irrigated conditioned. It is observed that out of 19 lines, considering plant height stress index, seventeen lines showed tolerance above the test crop (Titas). The lines HYM 11/BSi 427, HYM 12/BSi 467, EM 15/BSi 467 and BSi I showed better tolerance than the test crop when dry matter stress index was considered. Nine lines out of 19 showed better yield stability ratio as compared to test crop (Titas). It is observed that greater the tolerance index, larger is the yield gap between normal and stress condition. Considering all the parameters like PHSI, DMSI , TOL, YS ratio, drought susceptibility index and also the visual observation, the lines BSi-1, EM 15/ BSi 467 and EM 8 /BSi 467 showed better performance than the test crop. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18276 Bangladesh J. Sci. Ind. Res. 48(4), 265-270, 2013